Epistemologi Tafsir Fii Zhilalil Qur’an Karya Sayyid Qutb - Nor, Muhammad; Dahliana, Yeti (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
The epistemology of interpretation is a branch of science that aims to answer questions based on the theory of applied science about interpretation itself. The Book of Tafsir Fii Zhilalil Quran by Sayyid Qutb is one of the tafsir that was born in contemporary times using the tahlili method and has an al-adabi al-ijtimā'i pattern. This study aims to understand Sayyid Qutb's interpretive epistemology in interpreting the Koran in his work Tafsir Fii Zhilalil Koran. How can someone assess the validity of an interpretation based on epistemic rules? This research uses a qualitative approach and library research and examines both primary and secondary sources to descriptively analyze the biography of Sayyid Qutb, the epistemology of interpretation, the advantages and disadvantages of Fii Zhilalil's interpretation of the Qur'an. This research shows that this tafsir book attempts to provide a comprehensive interpretation of each text of the Qur'an in accordance with the orderly sequence of the mushaf. So this book of tafsir makes a contribution based on al-adabi al-ijtimā'i's style of interpretation, usually explaining several phenomena related to social and cultural developments at that time and providing solutions on how to overcome the social problems being faced by Muslims.